Resolving the Artisan Entrepreneur’s Oppositional Identity With Venturing in a Declining City Context - Wilkerson, James M. (American Journal of Management, 2021)
This article presents conceptual research questions and propositions on the relationship between the artisan entrepreneur’s oppositional identity and entrepreneurially venturing in the context of declining cities and urbanized regions. In general, I propose that some features of declining cities typically deemed harmful to business (e.g., deindustrialization, population loss, stifled innovation) may be less problematic for artisan ventures operated with a strong devotion to craft, localness and sense of place, and independence and less emphasis on financial performance than is typical of more mainstream entrepreneurship. The conceptual development herein relies on identity theory (including occupational identity and counter-institutional identity concepts), embeddedness theory, and urban economics concepts. This effort addresses calls for more research on both artisan entrepreneurship and the declining city as a context of entrepreneurship.